The effectiveness of a plant integrated lowcost treatment system to treat well water in coastal regions. Issue 11 (21st September 2022) - Rathnayaka, R. M. C. Y.; Amarathunga, A. A. D.; Bellanthudawa, B. K. A.; Rathnasri, P. A. S. A.; Novak, A. T.; Amarasiri, C.
Abstract: The present study aimed to quantify the treatment capacities of medicinal plant materials integrated into low-cost water treatments system (LCWTS) to treat well water in the coastal regions of Jaffna and Dikowita in Sri Lanka. Terminalia arjuna roots, Strychnos potatorum seeds, and Phyllanthus emblica leaves were employed to design LCWTS. Paired t-tests were performed to explore water quality parameters of well water before and after treatment. Treated well water was compared with the Sri Lanka Standard Institute and Central Environment Authority. The water quality parameters of treated water samples were significantly different ( p < 0.05) in three filter media. Further, ammonia, total hardness, and alkalinity concentrations in drinking water exceeded the tolerance limits. The most effective LCWTS was Terminalia arjuna while Strychnos potatorum seeds was the least effective LCWTS. Terminalia arjuna roots were the most effective filter medium due to its specific phytoremediation capabilities for water filtration and Phyllanthus emblica leaves were good in adsorbing contaminants in water. Hence, the present study showed that Terminalia arjuna and Phyllanthus emblica can be used as potential LCWTS to treat the water quality of total hardness, conductivity, ammonia, total suspended solids, alkalinity, and chloride concentrations. HIGHLIGHTS: Terminalia arjuna roots, Strychnos potatorum seeds, and Phyllanthus emblica leaves were used to design LCWTS. The most effective LCWTS was Terminalia arjuna for improving water quality in contaminated water. Phyllanthus emblica can be used as potential LCWTS to treat the water quality. Improve water quality parameters such as total hardness, conductivity, ammonia, total suspended solids, alkalinity, and chloride concentrations. Graphical Abstract